FAMILY HEALTH CARE FOR CHRONIC ILLNESS PEOPLE IN COMMUNITY: QUALITATIVE STUDY: none - Virasiri, Saovakon; Jenjaiwit, Patcharaporn (International Journal For Research In Health Sciences And Nursing, 2022)
Introduction: Chronic illness person has trouble in both body and mind, including family system. Therefore, health personnel should provide care for the whole family. However, there is less insight into family health care practice for families with chronic illness persons in community settings. Therefore, the study aimed at describing family health care practices for chronic illness persons from the participants ‘view. Method: Qualitative study was conducted. Participants included chronic illness persons, family members, healthcare personnel, and community leaders. Data collection consisted of in-depth interviews with tape recording, observation, note taking, and focused group interviews. Content analysis was done for data analysis. Findings: The findings displayed three major themes with nine subthemes in relation to the participants’ narration. First, “prioritizing personal illness severity for providing care at home.” Second, “common disease, more complication, difficult to control, and need special one to provide health care.” And third, the “community strongly participation, supports, follows up, and learns from patients and families’ styles.” Conclusion: The results support nurses and health personnel in gaining insight into family health care in the community setting based on the perception of patients, family members, health personnel, and community leaders. Therefore, an effective family health care model and intervention should thus be developed fitting to the needs and primary health care system.